Nasal dorsum reconstruction in the cutaneous oncology setting - Garrido,Pedro M. (2022)
Abstract The nose is one of the most frequent anatomic locations of skin cancer. The purpose of surgery is not only fully eliminating the tumor but also preserving nose function and aesthetics. Reconstruction of defects involving the nasal dorsum usually presents a substantial challenge. A wide range of reconstructive options have been developed for reconstructing this area, all of which can result in excellent outcomes. The choice of a reconstructive technique is influenced by tumor type, by the defect, by patient individual skin characteristics, and by surgeon preferences. Defects on the nasal dorsum frequently cross to adjacent cosmetic subunits, such as the nasal tip, the sidewall, the medial canthus, and the glabella. These complex defects usually require challenging reconstructive technique and carry a higher risk of local complications. In this article, the main reconstructive techniques for nasal dorsum reconstruction are reviewed.